ID: 17. Issue 1 (November 2015) - Pogue, Sarah; Taura, Tetsuya; Bi, Mingying; Mikesell, Glen; Yun, Yong; Sho, Angela; Behrens, Collette; Stevens, Maxwell; Domagala, Teresa; Sokolovsky, Maya; Hallak, Hussein; Rosenstock, Moti; et al.
<x xml:space="preserve">Abstract</x> Many cytokines have potential therapeutic applications and several, including type I interferons (IFN), have been approved for the treatment of cancer and/or autoimmune disease. While these agents are effective, they are associated with dose-limiting toxicities that prevent their use at levels sufficient to promote optimal therapeutic benefit. Thus, approaches which enhance the therapeutic index (TI) of cytokines are needed. A moderate degree of tumor-specificity may be achieved by attaching a cytokine such as IFN to a tumor-targeting antibody; such immunocytokines are highly active but show only moderate tumor-specificity since the cytokine is still active on antigen-negative cells. We sought to improve the TI of antibody-targeted cytokines by mutating the cytokine portion to significantly reduce its affinity for its receptor, thereby making it dependent on antibody-targeting. Here we demonstrate that such molecules, consisting of attenuated cytokines (Attenukines™) attached to tumor-targeting antibodies, are 1000–100, 000-fold more potent on antigen-positive cells compared to antigen-negative (normal) cells. This is shown for antibody-Attenukine™ fusion proteins based on multiple tumor antigens (CD20, CD38, CD138, HMW-MAA, HLA) and multiple attenuated mutants of IFN, IFN, IL-4 and IL-6. Furthermore, we have evaluated an anti-CD38-attenuated IFN molecule (anti-CD38-Attenukine™) in various CD38+ myeloma xenograft models and found that this molecule retains potent specific anti-tumor efficacy. Moreover, in non-human primates, we have confirmed that the attenuating mutation in IFN indeed decreases non-targeted IFN biomarker responses by greater than 100-fold. Our findings suggest that the administration of antibody-attenukines™ to cancer patients may promote robust cytokine-dependent tumor-killing while minimizing systemic toxicity.